The Effect of Baltic Dry Index, Gold, Oil and USA Trade Balance on Dow Jones Sustainability Index World - Giannarakis, Grigoris; Lemonakis, Christos; Sormas, Asterios; Georganakis, Christos (International Journal of Economics and Financial Issues, 2017)
The predictability of stock returns by investors has been a crucial issue updating over the time. The aim of this study is to investigate the effect of economic leading indicator of Baltic Dry Index (BDI) on stock returns of socially responsible stock index. For the purpose of the study, Dow Jones Sustainability Index World (DJSIW) is employed in the proposed model so as to detect the world’s leading companies that incorporate business initiatives consistent to sustainable development. It incorporates the generalized autoregressive conditional heteroskeasticity model in methodology for the period of October 1999 to July 2016 using monthly data. The empirical results revealed that BDI affect positively DJSIW implying that the maritime shipping cost as a proxy of economic growth affects the stock returns of socially responsible companies. In addition, gold, oil and the US trade balance tend to affect positively the DSJIW. The results are useful to investors in order to set their investment portfolio and management risk strategy. Keywords: Stock returns, Baltic Dry Index, gold, oil JEL Classifications: